Substantiation of Estimation Methods of Technogenic Noise Impact in Cadastral Value Determination of Land Plots - Elena Bykowa; Ivan Raguzin (Land, 2024)
This article presents a substantiation of methods for assessing the impact of anthropogenic noise pollution for land taxation. Statistical analyses have been carried out in order to establish the dependence of the market value of land plots for residential development in St. Petersburg on noise pollution caused by transport infrastructure facilities. The obtained data allowed us to conclude that in the modern conditions of the imperfect market, the considered factor is externalized. When finding the dependence, it can be included in the economic–mathematical model of cadastral value determination as an internal factor of the market, thus ensuring the principle of fairness of taxation. The lack of market reaction dictates the need to internalize negative environmental externalities through state regulation of land redistribution or redistribution of the tax burden between land rightholders and rightholders of objects that create noise.